Barkadahan a study of peer group norms and values among Filipino adolescents - Lajom, Jennifer Ann; Canoy, Nico; Amarmani, Rajiv; Parcon, Apryl Mae; Valera, Paula Melizza (Quezon City Psychological Association of the Philippines.)
"Peer groups are among the most influential aspects of adolescent development. The present study is a qualitative investigation of the behaviors, norms, values, and dynamics in general of the adolescent peer group in the Filipino setting-the barkada."
Keywords: Adolescence; Identity development; Group norms; Values